2011
DOI: 10.1016/j.neuroimage.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of amyloid plaques targeted by USPIO-Aβ1–42 in Alzheimer's disease transgenic mice using magnetic resonance microimaging

Abstract: Amyloid plaques are one of the pathological hallmarks of Alzheimer's disease (AD). The visualization of amyloid plaques in the brain is important to monitor AD progression and to evaluate the efficacy of therapeutic interventions. Our group has developed several contrast agents to detect amyloid plaques in vivo using magnetic resonance microimaging (μMRI) in AD transgenic mice, where we used intra-carotid mannitol to enhance blood brain barrier (BBB) permeability. In the present study, we used ultrasmall super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 56 publications
1
128
1
1
Order By: Relevance
“…On the other hand, other groups have shown the feasibility of using high-resolution microscopic MR imaging to detect single amyloid plaques (1,9,(24)(25)(26). This approach, however, lacks sensitivity and specificity as signal voids originating from T 2 -or T 2 *-weighted MR imaging may be related to blood vessels oriented in the orthogonal direction relative to the imaging plane or to microhemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other groups have shown the feasibility of using high-resolution microscopic MR imaging to detect single amyloid plaques (1,9,(24)(25)(26). This approach, however, lacks sensitivity and specificity as signal voids originating from T 2 -or T 2 *-weighted MR imaging may be related to blood vessels oriented in the orthogonal direction relative to the imaging plane or to microhemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was able to be shown that early stages of post-radiogenic brain damage can be imaged via targeted SPIO-AB against ICAM-1 [183]. With respect to the use of SPIO in the imaging of neurodegenerative diseases such as Alzheimer's disease, amyloid beta plaques were able to be successfully addressed via MION-AB [184] or SPIO-AB against amyloid-beta 42 [185]. …”
Section: Imaging Of Multiple Sclerosis (Ms) and Neurodegenerationmentioning
confidence: 99%
“…SPION coupled NPs were tested by in vitro imaging of Aβ-related aggregates [155] and in vivo with a transgenic AD mouse model [156][157][158]. This type of approach by coupling Aβ-targeting antibodies to NPs give rise to the question of a double function of such nanocarriers which could have positive side-effect capturing toxic protein species, and activating elimination pathways adding a possible therapeutic action [159][160][161].…”
Section: Therapeutic Strategies Using Nanoparticles In Ndmentioning
confidence: 99%